Work, Change and Workers - Billett, Stephen. author. aut Link
XII, 286 p.
Keywords: This book provides a fresh account of the changing nature of work and how workers are changing as result of the requirements of contemporary working life. It explores the implications for preparing individuals for work and maintaining their skills throughout working life. This is done by examining the relations between the changing requirements for working life and how individuals engage in work. An analysis that engages the psychological, sociological, philosophical and anthropological literatures as they relate to work as well as recent empirical research that examines and elaborates perspectives of work and work practice as social institutions and as a vocation that individuals exercise with intentionality and agency. So a key basis for considering changing work and changing workers is the relationships between the social institutions and cultural needs and practices that necessitates and constitutes paid work and how individuals engage and elect to participate and learn in that work. Implications for vocational education, professional development and on-going learning throughout working life are addressed. These include developing skills in educational institutions, workplaces, and combinations thereof and in times when both government and employers are looking for others to sponsor that development and maintaining the competence and engagement of older workers.